The fundamental human response to wind-induced building motion. Issue 165 (June 2017) - Lamb, S.; Kwok, K.C.S.
Abstract: This paper identifies seven areas where an increase in our fundamental understanding of the human response to building motion will facilitate the design of next-generation serviceability criteria for wind-induced building motion. These advances in knowledge address: (1) understanding the effects of wind-induced building motion on occupants, (2) metrics for building performance assessment, (3) understanding of habituation to building motion, (4) potential and real benefits of education, (5) motion characteristics to predict adverse occupant effects, (6) differentiation between residential and office serviceability criteria, and (7) multidisciplinary research methods and measures used in occupant comfort research. Each is discussed with reference to engineering literature and incorporates a multidisciplinary perspective including psychological and physiological research. Finally, methodological issues in the occupant comfort literature are discussed and recommendations for future research are offered to facilitate the design of next-generation serviceability criteria for wind-induced building motion. Highlights: Wind-induced building motion adversely affects occupant wellbeing and performance. Seven areas needing fundamental research are identified. Multidisciplinary research is presented for each area.